ANALISIS TINGKAT PENCEMARAN UDARA DI KECAMATAN WANEA KOTA MANADO - Rendy Sangga; Bobby Polii; Aneke Tarore (Universitas Sam Ratulangi, 2021)
ABSTRAKAir is a mixture of several types of gases whose ratio is not fixed, depending on the stateof air temperature, air pressure and the surrounding environment. Air pollution is the presenceof one or several contaminants in the atmospheric air, such as dust, foam, gas, fog, smells ofsmoke or vapor in large quantities with various properties or duration in the air, so that theycan cause disturbances to the life of humans, plants or animals or objects or without clearreasons can already affect the sustainability of the life of organisms and objects. This researchwas conducted for one month, from August to September 2020. The research site wasconducted at the air quality observation station in the Provincial Environmental Service. Airquality measurement results. The tools used are computers, writing instruments and a camera.The research method used is secondary data analysis (collecting data and analyzing secondarydata). The gas concentrations in ambient air in Wanea District, Manado City each have thefollowing ranges: SO2 is 10 Î¼g / Nm3 - 18 Î¼g / Nm3; NO2 is 1 Î¼g / Nm3-95Î¼g / Nm3 and COis 20-923 Î¼g / Nm3. The maximum concentrations of SO2, NO2 and CO gases in the ambientair in Wanea District, Manado City are below the required quality standard.Kata Kunci: Pencemaran Udara Di Kota Manado